210 Syndecan-4/fgf-2/pkca signalling regulates vascular smooth muscle cell calcification via cross-talk with tgfb. (5th June 2017) - Borland, Samantha; Borland, Shona; Morgan, Mark; Francis, Sheila; Merry, Catherine; Canfield, Ann
Abstract : Vascular smooth muscle cells (VSMCs) were induced to mineralise with β-glycerophosphate (β-GP). Controls were cultured without β-GP. FGF-2 mRNA (~40-fold increase, P<0.001) and protein (~2-fold increase, P<0.05) expression are significantly increased in mineralising VSMCs. FGF-2 also localises to sites of calcification within human atherosclerotic plaques. The expression of syndecan-4, a heparan sulphate proteoglycan which acts as a co-receptor for FGF-2 signalling, is also increased in mineralising VSMCs (~5-fold, P<0.001) and co-localizes with FGF-2 in human calcified atherosclerotic plaques. Exogenous FGF-2 inhibits VSMC mineralisation (P<0.001) and this inhibition is reduced when syndecan-4 expression is knocked-down using siRNA. Biochemical inhibition of FGFR signalling using a pan FGFR inhibitor (BGJ398) increases transforming growth factor-β1 (TGFβ1)-induced Smad2 phosphorylation in VSMCs. As TGF β1 increases mineral deposition by VSMCs (~2-fold, P<0.01), the relationship between FGF and TGFβ signalling in VSMC mineralisation was investigated. Inhibiting FGFR signalling using BGJ398 or knocking-down syndecan-4 expression in VSMCs using siRNA increases VSMC mineralisation (both P<0.001). These increases are prevented by inhibiting TGFÎ 2 signalling with SB431542, suggesting cross-talk between FGF-2 and TGFÎ 2 signalling is crucial for the regulation of VSMC mineralisation. Syndecan-4 can also regulate FGF-2 signalling via protein kinase Cα (PKCα) activation. Biochemical inhibition of PKCα activity using G6976, or knocking-down PKCα expression increases VSMC mineralisation (both P<0.05); this increase is also prevented with SB431542. Finally, the ability of FGF-2 to inhibit VSMC mineralisation is reduced when PKCα expression is knocked-down. In conclusion, our study has identified that syndecan-4/FGF-2 signalling is up-regulated in mineralising VSMCs to reduce TGFÎ 2 signalling and minimise further calcification. Syndecan-4 regulates FGF-2 signalling to prevent excessive mineralisation by (a) acting as a co-receptor for FGF-2 and inducing downstream signalling via FGFR and (b) interaction with PKα. The syndecan-4/FGF-2/TGFα signalling axis could therefore represent a new therapeutic target for vascular calcification.